Perinatal Outcome of Second Twin in Third Trimester of Pregnancy - Baral, Pramisha; Dangal, Ganesh; Baral, Gehanath; Subedi, Kirtipal (Journal of Nepal Health Research Council, 2021)
Background: With increasing trend of twin pregnancy and along with increasing advancement in neonatal care, survival rate of twin pregnancy has increased. However there is worse perinatal outcome in second twin in comparison with the first twin. Methods: Hospital based observational cross-sectional study of 42 pregnant women with twin pregnancy at Paropakar Maternity and Women’s Hospital was conducted from November 2019 to October 2020. The outcome of second twin was assessed in relation to gestational age, chorionicity, mode of delivery, delivery interval. McNemar test was used for analysis with 0.05 as the level of significance. Results: Among 42 pair of twins, Apgar score of the second twin was found to be lower than the first twin (p=0.00) in general and in preterm gestation (p=0.115). Among twin who had monochorionic placenta; higher number of twin 1 had Apgar score of ?7(p=0.004). Among twin who had inter-delivery interval of <30min; higher number of twin1 had Apgar score of ?7 at 5 minutes. (p=0.00). Conclusions: Second twin has lower Apgar score in relationship to period of gestation, mode of delivery, inter-delivery interval, and chorionicity. Keywords: Apgarscore; chorionicity; twin pregnancy